The Problem of Regional Inequality in Social and Economic Development of the Russian Federation - N. E. Bondarenko; R. V. Gubarev (Вестник Российского экономического университета имени Г. В. Плеханова)
Today’s social and economic development of Russian regions is characterized by extreme unevenness and depends on many factors affecting the potential possibilities of the territory. Proceeding from this fact, the article studies key economic trends, which research theoretical foundations of regional growth and territorial development, reveals their main idea and identifies factors influencing the development of regions in order to use them in the analysis of Russian regional inequality. The authors investigate differentiation of Russian regions’ inequality by a number of social and economic parameters and distinguish groups of regions, which gives an opportunity to discover key factors of their development and find reasons for their backwardness. On the basis of the comparative analysis they came to the conclusion that territorial polarization of Russian regions goes on rising, mainly in wages, investment budget revenues, while investment concentration is still observed in regions with max competitive advantages, i. e. high agglomeration and rich in raw materials. According to the authors, these problems can be resolved by complex measures of state policy, which have both general regional and selective nature. For each group of regions lines of selective regional policy were put forward, which could effectively smooth regional disproportions and promote the development of economy as a whole.